CORONAVIRUS DISEASE AND IMMUNOTHERAPY IN JUVENILE IDIOPATHIC ARTHRITIS - Jovanović, Nikola; Jordanović, Milica; Vojinović, Jelena; Manojlović, Milena (Acta medicae Medianae, 2024)
The COVID-19 pandemic was a huge challenge to paediatricians around the world. Patients with juvenile idiopathic arthritis (JIA) and COVID-19 infection could present a potential ethical and medical dilemma. Here we discuss the results of a medical survey made on the parents of children with JIA. Our primary aim was to determine if there was a significant difference in the number of flares of JIA after COVID-19 infection between the group of children who were receiving biological drugs and children not receiving biologicals. Other goals were to investigate the parents’ motivation to vaccinate children against SARS-CoV-2 and to determine the most frequent symptoms of COVID-19 infection in these children. A retrospective study was based on the data of a telephone survey conducted between March 10, 2022, and May 12, 2022, including 65 paediatric patients with JIA. The data were provided from the Heliant Health information system database. In children who tested positive for SARS-CoV-2, the most frequent symptom was fever, followed by upper respiratory symptoms. Four flares of JIA were observed in the group of children on biological therapy, while in the group without biologicals two flares followed the COVID-19 infection. The parents’ motivation for vaccination against SARS-CoV-2 was extremely low. Our survey-based research did not find a significant difference regarding the COVID-19 infection between children with JIA on biologicals and children with JIA not receiving biologicals, but it did emphasise the parents’ hesitancy about vaccination. We propose building a unique database for patients with the diagnosis of JIA which could improve the quality of life of these patients.
Keywords: coronavirus disease, juvenile idiopathic arthritis, severe acute respiratory syndrome coronavirus 2, flare, biologicals